So, Dear Applicant, Do You Mean Working from Home or Shirking from Home? - Eline Moens; Elsy Verhofstadt; Luc Van Ootegem; Stijn Baert (Institute of Labor Economics (IZA), 2023)
Many applicants want a job with the possibility of telework. However, the literature is unclear on whether being explicit about this wish and the reason for it leads to negative consequences on hiring intentions. In this paper we therefore investigate how expressing a desire for telework, for work-life balance and for productivity in particular, impacts the probability of receiving an interview and what it signals to recruiters. To this end, we set up a state-of-the-art vignette experiment in which recruiters evaluate fictitious applicants for different jobs. As a result of this experimental set-up, the answers to our research questions can be interpreted causally, and external validity benefits from the heterogeneity of the jobs. We find that if the desire for work-life balance is the stated motivation, the preference is punished more severely than if the motivation is productivity. Compared to applicants who do not mention a preference for telework, recruiters are 5.1 percentage points less inclined to invite applicants who pronounce this desire for work-life balance to an interview and 2.1 percentage points less inclined to invite applicants for whom the motivation is productivity. Lastly, mentioning a telework preference for work-life balance has a clear negative effect on anticipated achievement striving, commitment, and availability.
Keywords: M51; M54; J22; J32; J63; J81; 330; telework; interview probability; factorial survey experiment